Challenges of Digital Transformation of Makassar City Government in the Framework of E-Government - Asmansyah Asmansyah; A. Hadijah Sulfiyani A (Journal of Public Policy and Local Government (JPPLG), 2026)
Digital transformation in government has become an essential part of improving public service quality, bureaucratic effectiveness, and governmental transparency at the local level. The Government of Makassar City is considered one of the regions actively developing digital based public services through the implementation of e-government, smart governance, and the Electronic Based Government System (SPBE). This study aims to analyze the challenges of digital transformation within the Makassar City Government in the framework of e-government and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach using a library research method through the analysis of scientific journals and related documents concerning governmental digital transformation. The findings indicate that the Makassar City Government has experienced significant progress in implementing digital services, particularly in population administration, public services, and the strengthening of information technology based governance systems. However, the digital transformation process still faces several challenges, including limited interagency data integration, inadequate digital human resource capacity, gaps in public digital literacy, regulatory changes, as well as issues related to data security and information technology infrastructure. This study also found that the success of digital transformation in Makassar remains sectoral and has not been fully integrated into a sustainable digital governance framework. Therefore, stronger coordination among regional institutions, improvement of bureaucratic competence, development of digital infrastructure, and optimization of SPBE implementation are required to ensure that governmental digital transformation can operate more effectively, inclusively, and sustainably.